Taiwan's Response to Influenza: A Seroepidemiological Evaluation of Policies and Implications for Pandemic Preparedness. (August 2022) - Ho, Pui-I; Liu, Wei; Li, Tiger Zheng-Rong; Chan, Ta-Chien; Ku, Chia-Chi; Lien, Yu-Hui; Shen, Yea-Huei Daphne; Chen, Juine-Ruey; Yen, Muh-Yong; Tu, Yu-Kang; Lin, Wan-Yu; Compans, Richard; et al.
ABSTRACT: Objectives: To evaluate class suspension and mass vaccination implemented among Taipei schoolchildren during the 2009 influenza pandemic and investigate factors affecting antibody responses. Methods: We conducted 2 cohort studies on: (1) 972 schoolchildren from November 2009–March 2010 to evaluate pandemic policies and (2) 935 schoolchildren from November 2011–March 2012 to verify factors in antibody waning. Anti-influenza H1N1pdm09 hemagglutination inhibition antibodies (HI-Ab) were measured from serum samples collected before vaccination, and at 1 and 4 months after vaccination. Factors affecting HI-Ab responses were investigated through logistic regression and generalized estimating equation. Results: Seroprevalence of H1N1pdm09 before vaccination was significantly higher among schoolchildren who experienced class suspensions than those who did not (59.6% vs 47.5%, p<0.05). Participating in after-school activities (adjusted odds ratio [aOR]=2.47, p=0.047) and having ≥3 hours per week of exercise (aOR=2.86, p=0.019) were significantly correlated with H1N1pdm09 infection. Two doses of the H1N1pdm09 vaccine demonstrated significantly better antibody persistence than 1 dose (HI-Ab geometric mean titer: 132.5 vs 88.6, p=0.047). Vaccine effectiveness after controlling for preexisting immunity was 86% (32%-97%). Exercise ≥3 hours per week and preexisting immunity were significantly associated with antibody waning/maintenance. Conclusions: This study is the first to show that exercise and preexisting immunity may affect antibody waning. Further investigation is needed to identify immune correlates of protection.